2022
DOI: 10.1124/jpet.122.001277
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2B6 Pharmacogenetics on Stereoselective Inhibition and Induction of Bupropion Metabolism by Efavirenz in Healthy Volunteers

Abstract: We investigated the acute and chronic effects of efavirenz, a widely used antiretroviral drug, and CYP2B6 genotypes on the disposition of racemic and stereoisomers of bupropion (BUP) and its active metabolites, 4-hydroxyBUP, threohydroBUP and erythrohydroBUP. The primary objective of this study was to test how multiple processes unique to the efavirenz-CYP2B6 genotype interaction influence the extent of efavirenz-mediated drug-drug interaction (DDI) with the CYP2B6 probe substrate BUP.In a three-phase, sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The frequency of CYP2B6 diplotypes in the cohort ( 1 for plasma and in Table 2 for urine. Disposition was highly stereoselective, as observed previously for single-dose (Kharasch et al, 2008;Masters et al, 2016;Kharasch and Crafford, 2019;Gufford et al, 2022) and steady-state (Kharasch et al, 2020) CYP2B6*6 (516G>T, rs3745274 and 785A>G, rs2279343) is the most common and most extensively studied CYP2B6 variant, and eliciting lower protein expression due to the 516G>T single nucleotide variant causing an amino acid change and aberrant splicing (Hofmann et al, 2008). The 516G>T single nucleotide variant is however also found in numerous other CYP2B6 alleles, and is considered a canonical decreased function allele.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The frequency of CYP2B6 diplotypes in the cohort ( 1 for plasma and in Table 2 for urine. Disposition was highly stereoselective, as observed previously for single-dose (Kharasch et al, 2008;Masters et al, 2016;Kharasch and Crafford, 2019;Gufford et al, 2022) and steady-state (Kharasch et al, 2020) CYP2B6*6 (516G>T, rs3745274 and 785A>G, rs2279343) is the most common and most extensively studied CYP2B6 variant, and eliciting lower protein expression due to the 516G>T single nucleotide variant causing an amino acid change and aberrant splicing (Hofmann et al, 2008). The 516G>T single nucleotide variant is however also found in numerous other CYP2B6 alleles, and is considered a canonical decreased function allele.…”
Section: Resultsmentioning
confidence: 54%
“…Metabolism in vitro to the more recently identified metabolite 4'-hydroxybupropion, and secondary metabolites 4'-hydroxy-erythrohydrobupropion and 4'-hydroxy-threohydrobupropion is also stereoselective (Sager et al, 2016a;Sager et al, 2016b). Prior human in vivo investigations showed that single-dose (Kharasch et al, 2008;Masters et al, 2016;Gufford et al, 2022) and steady-state (Kharasch et al, 2020) bupropion disposition in humans is also stereoselective. The clinical importance of metabolite formation 6 has been recognized for smoking cessation and antidepressant therapy (Lee et al, 2007;Zhu et al, 2012;Laib et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that most of the studies that analyze CYP2B6 activity were conducted using some kind of surrogate endpoint, such as efavirenz plasma concentration, or were performed on tissues such as peripheral blood cells or healthy donor hepatocytes cell culture [ 22 , 24 , 26 ]. One of the few studies performed on human liver tissue samples in a population of HCV mono-infected patients by Drozdzik et al showed that there was down-regulation of a couple of CYP enzymes, but the level of CYP2B6 remained unchanged [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We chose bupropion, a CYP2B6-sensitive probe substrate 11 , to examine the CYP2B6 activity in vitro . The objective of this study was to determine how much silybin inhibits CYP2B6 activity and protein expression in an in vitro study.…”
Section: Introductionmentioning
confidence: 99%